Pengaruh Berbagai Kompos Daun Legume dan Mikroba Terhadap Serapan Hara dan Petumbuhan Semai Eboni - Lukman, M Nikwanul; Yusran, Yusran; Wulandari, Retno (Universitas Tadulako, 2023)
The research aims to find out how much influence legume leaf compost and microbes on improving nutrient absorption andgrowth of ebony seedlings. The research was conducted from August 2, 2022 to February 2, 2023 for 6 months at the BPDAS Palu-Poso Permanent Nursery. The compost used is compost derived from legume leaves consisting of gamal, lamtoro, and turi trees and the microbes used are Plant Growth Promoting Rhizobacteria (PGPR) and Plantarum Plant Growth Stimulant (PPGS) which are microbes that are widely traded in agricultural specialty online stores, The samples of this study amounted to 108 ebony seedlings with 12 treatments andeach treatment contained 9 seedlings/samples. This study used analysis of variance of complete randomized design (CRD) to determine the significant and non-significant effects of each treatment by looking at several variables from height, diameter, number of leaves, sturdiness, nutrient uptake, seedling quality index in each seedling/sample. The results showed that seedlings treated with tailings soil + lamtoro leaf compost + PGPR microbes (K3M2) had the best average growth in each variable. While the lowest growth of seedlings with control soil treatment (K0M0).